2020
DOI: 10.1186/s12917-020-02461-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of buccal damage associated with acute inhalation exposure to 2,4-dichlorophenoxyacetic acid (2,4-D) in mice

Abstract: Background: The herbicide dichlorophenoxyacetic acid (2,4-D) is one of the most widely used crop spraying products in the world. Some pesticides induce the degranulation of mast cells and increase allergic responses. This is the first study to evaluate the damage to the oral mucosa after an experimental simulation of environmental inhalation exposure to the 2,4-D herbicide. The aim of this study was evaluate the possible oral damage caused by acute inhalation exposure to the herbicide 2,4-D. Results: There was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…While studies carried out with rodents evaluating the oral cavity after acute inhalation exposure ( 18 ) and chronic oral and inhalation exposure ( 11 ) showed an increase in tongue epithelium thickness, mainly with an increase in the concentration of 2,4-D, our study did not show an increase in esophagus epithelial thickness. Instead, in our study, 100% of the animals in the groups exposed to the moderate oral concentration and the high inhalation concentration of 2,4-D had hyperkeratosis, and these were the groups with the lowest epithelial thickness.…”
Section: Discussioncontrasting
confidence: 86%
“…While studies carried out with rodents evaluating the oral cavity after acute inhalation exposure ( 18 ) and chronic oral and inhalation exposure ( 11 ) showed an increase in tongue epithelium thickness, mainly with an increase in the concentration of 2,4-D, our study did not show an increase in esophagus epithelial thickness. Instead, in our study, 100% of the animals in the groups exposed to the moderate oral concentration and the high inhalation concentration of 2,4-D had hyperkeratosis, and these were the groups with the lowest epithelial thickness.…”
Section: Discussioncontrasting
confidence: 86%
“…These data show that GBH can stimulate an oral allergic reaction, especially after direct contact and in females. Studies evaluating other herbicides demonstrated that herbicides may be systemic allergens (Cushman and Street 1982;Yasunaga et al 2015) and are allergenic to the skin, respiratory tract (Fukuyama et al, 2009) and oral cavity (Parizi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…NORs are markers of cell proliferation (Parizi et al 2020). An increase in the number of NORs in the mucosa of the tongue observed in the groups exposed to GBH indicates toxicity to the oral epithelium that stimulated cell proliferation to repair possible cell destruction caused by GBH.…”
Section: Discussionmentioning
confidence: 99%
“…In oral and inhalation exposure, the oral cavity is the first line of contact with agrochemicals [ 26 ]. Therefore, it is necessary to describe the biological and chemical characteristics of the oral cavity to subsequently analyze its interaction with pesticides.…”
Section: General Characteristics Of Pesticidesmentioning
confidence: 99%
“…Thus, microorganisms are also removed during this turnover, thereby limiting bacterial growth, and stabilizing the oral biofilm [ 27 , 28 , 30 , 34 , 35 ]. However, pesticide contact has been shown to increase lesions in these epithelium [ 26 ].…”
Section: Oral Cavitymentioning
confidence: 99%